Quantitative evidence for conserved longevity pathways between divergent eukaryotic species - Smith, Erica D.; Tsuchiya, Mitsuhiro; Fox, Lindsay A.; Dang, Nick; Hu, Di; Kerr, Emily O.; Johnston, Elijah D.; Tchao, Bie N.; Pak, Diana N.; Welton, K. Linnea; Promislow, Daniel E.L.; Thomas, James H.; et al. (Genome Research, 2008)
Studies in invertebrate model organisms have been a driving force in aging research, leading to the identification of many genes that influence life span. Few of these genes have been examined in the context of mammalian aging, however, and it remains an open question as to whether and to what extent the pathways that modulate longevity are conserved across different eukaryotic species. Using a comparative functional genomics approach, we have performed the first quantitative analysis of the degree to which longevity genes are conserved between two highly divergent eukaryotic species, the yeast Saccharomyces cerevisiae and the nematode Caenorhabditis elegans. Here, we report the replicative life span phenotypes for single-gene deletions of the yeast orthologs of worm aging genes. We find that 15% of these yeast deletions are long-lived. In contrast, only 3.4% of a random set of deletion mutants are long-lived—a statistically significant difference. These data suggest that genes that modulate aging have been conserved not only in sequence, but also in function, over a billion years of evolution. Among the longevity determining ortholog pairs, we note a substantial enrichment for genes involved in an evolutionarily conserved pathway linking nutrient sensing and protein translation. In addition, we have identified several conserved aging genes that may represent novel longevity pathways. Together, these findings indicate that the genetic component of life span determination is significantly conserved between divergent eukaryotic species, and suggest pathways that are likely to play a similar role in mammalian aging.